```Question 269013
40x+26y=486.7_20x+31y=332.42

&#9658;Since 26y does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 26y from both sides.
40x=-26y+486.7_20x+31y=332.42

&#9658;Divide each term in the equation by 40.
(40x)/(40)=-(26y)/(40)+(486.7)/(40)_20x+31y=332.42

&#9658;Simplify the left-hand side of the equation by canceling the common terms.
x=-(26y)/(40)+(486.7)/(40)_20x+31y=332.42

&#9658;Combine the numerators of all expressions that have common denominators.
x=(-26y+486.7)/(40)_20x+31y=332.42

&#9658;Replace all occurrences of x with the solution found by solving the last equation for x.  In this case, the value substituted is ((-26y+486.7))/(40).
x=(-26y+486.7)/(40)_20((-26y+486.7)/(40))+31y=332.42

&#9658;Remove the parentheses around the expression -26y+486.7.
x=(-26y+486.7)/(40)_20((-26y+486.7)/(40))+31y=332.42

&#9658;Divide each term in the numerator by the denominator.
x=-(26y)/(40)+(486.7)/(40)_20((-26y+486.7)/(40))+31y=332.42

&#9658;Reduce the expression -(26y)/(40) by removing a factor of 2 from the numerator and denominator.
x=-(13y)/(20)+(486.7)/(40)_20((-26y+486.7)/(40))+31y=332.42

&#9658;Divide 486.7 by 40 to get 12.17.
x=-(13y)/(20)+12.17_20((-26y+486.7)/(40))+31y=332.42

&#9658;Remove the parentheses around the expression -26y+486.7.
x=-(13y)/(20)+12.17_20((-26y+486.7)/(40))+31y=332.42

&#9658;Divide each term in the numerator by the denominator.
x=-(13y)/(20)+12.17_20(-(26y)/(40)+(486.7)/(40))+31y=332.42

&#9658;Reduce the expression -(26y)/(40) by removing a factor of 2 from the numerator and denominator.
x=-(13y)/(20)+12.17_20(-(13y)/(20)+(486.7)/(40))+31y=332.42

&#9658;Divide 486.7 by 40 to get 12.17.
x=-(13y)/(20)+12.17_20(-(13y)/(20)+12.17)+31y=332.42

&#9658;Multiply 20 by each term inside the parentheses.
x=-(13y)/(20)+12.17_(-13y+243.35)+31y=332.42

&#9658;Since -13y and 31y are like terms, subtract 31y from -13y to get 18y.
x=-(13y)/(20)+12.17_18y+243.35=332.42

&#9658;Since 243.35 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 243.35 from both sides.
x=-(13y)/(20)+12.17_18y=-243.35+332.42

&#9658;Add 332.42 to -243.35 to get 89.07.
x=-(13y)/(20)+12.17_18y=89.07

&#9658;Divide each term in the equation by 18.
x=-(13y)/(20)+12.17_(18y)/(18)=(89.07)/(18)

&#9658;Simplify the left-hand side of the equation by canceling the common terms.
x=-(13y)/(20)+12.17_y=(89.07)/(18)

&#9658;Divide 89.07 by 18 to get 4.95.
x=-(13y)/(20)+12.17_y=4.95

&#9658;Replace all occurrences of y with the solution found by solving the last equation for y.  In this case, the value substituted is 4.95.
x=-(13(4.95))/(20)+12.17_y=4.95

&#9658;Multiply -13 by 4.95 in the numerator.
x=(-13*4.95)/(20)+12.17_y=4.95

&#9658;Multiply -13 by 4.95 to get -64.33.
x=(-64.33)/(20)+12.17_y=4.95

&#9658;Move the minus sign from the numerator to the front of the expression.
x=-(64.33)/(20)+12.17_y=4.95

&#9658;Divide -64.33 by 20 to get -3.22.
x=-3.22+12.17_y=4.95

&#9658;Add 12.17 to -3.22 to get 8.95.
x=8.95_y=4.95

&#9658;This is the solution to the system of equations.
=&#9658; x=8.95_y=4.95```